Strengthening the Authority of Police Investigators in Addressing Criminal Offenses of Disseminating False News in the Digital Era - Apri Aji Setyawan; Megawati Barthos (Riviera Publishing, 2024)
The rapid advancement of digital technology has made the dissemination of false news a significant global issue, posing threats to social, political, and economic stability. This research investigates the challenges faced by police investigators in combating the criminal offense of disseminating false news in Indonesia and proposes innovative solutions to strengthen their authority. Using a normative juridical research method, the study explores legal, institutional, and technical factors contributing to investigative inefficiencies. Key issues identified include outdated legal frameworks, limited investigator capacity, weak organizational structures, and insufficient inter-agency collaboration. The study’s novelty lies in its multi-faceted approach to addressing these gaps. It proposes revising legal regulations to align with evolving technological dynamics, establishing more precise definitions of false news, and strengthening legal obligations for social media platforms. Additionally, the research highlights the importance of specialized training and professional certification for police investigators to enhance their technical and investigative skills. An advanced organizational structure is recommended, including the creation of a dedicated cybercrime unit equipped with state-of-the-art technology and international cooperation capabilities. To ensure transparency and accountability, the study also suggests implementing a robust oversight mechanism to monitor investigative actions, prevent abuse of authority, and foster public trust. By integrating these strategies, the proposed solutions aim to create a more effective and technology-responsive law enforcement system capable of addressing the complex challenges posed by the dissemination of false news in the digital age. These recommendations contribute to the broader discourse on modernizing law enforcement in an increasingly digitalized world.